HLA-DR expression on regulatory T cells is closely associated with the global immune activation in HIV-1 infected subjects naive to antiretroviral therapy - Xiao, Jian; Qian, Ke-lei; Cao, Qing-hua; Qiu, Chen-li; Qiu, Cao; Xue, Yi-le; Zhang, Xiao-yan; Zhong, Ping; Xu, Jian-qing; Li, Ming-yuan; Wang, Ying (Chinese medical journal, 2011)
Background The frequencies of regulatory T cells （Tregs） increased over the HIV infection but its counts actually decreased. We proposed that the decrease of Treg counts may cause the reduction of inhibitory effect and thereby account for the over-activation of Tregs during HIV infection. However, it remains unknown whether Tregs are also over-activated and thereafter the activation induced death may lead to the decrease of Tregs. Methods Tregs were defined as CD4＋CD25＋CD127lo/-T cells. Eighty-one HIV-1 infected patients were enrolled in our study, and twenty-two HIV-1 seronegative donors were recruited as the control. The levels of HLA-DR on Tregs were determined by FACSAria flow cytometer. Results Compared to HIV-1 seronegative donors, the levels of HLA-DR on CD4＋CD25＋CD127lo/- Tregs were significantly increased in HIV-1 infected patients, and its increase was positively associated with viral loads （r=0.3163, P=-0.004） and negatively with CD4 T-cell counts （r=-0.4153, P 〈0.0001）. In addition, significant associations between HLA-DR expression on CD4＋CD25＋CD127lo/- Tregs and the percentages of HLA-DR, CD38, Ki67 expressing CD4＋ and CD8＋ T cells were also identified. Conclusion HLA-DR on Tregs is a good marker for viral replication and disease progression. The over-activation of Tregs might result in the decrease of Tregs.